134k views
4 votes
An equation is shown below:

(4x − 1) + (2x + 2) = 1

Which statement shows a correct next step in solving the equation? (1 point)

Group of answer choices

The equation can become 6x + 1 = 1 by combining like terms.

The equation can become 3x + 4x = 1 by solving the terms in the brackets.

The equation can become 3x + 4x = 1 by applying the associative property of multiplication.

The equation can become 6x + 1 = 1 by applying the distributive property.

2 Answers

5 votes

Answer:

The first statement

Explanation:

By removing the parentheses, you get 4x - 1 + 2x + 2 = 1, and by adding like terms: 6x + 1 = 1.

User Kamidu Punchihewa
by
5.5k points
4 votes

Answer:

Answer: First option is correct.

A

Explanation:

Since we have given that

First step is to collect the like terms together :

The equation can become 6x + 1 = 1 by combining like terms.

On the other hand we didn't apply distributive property.

Hence, First option is correct.

Explanation:

User Joseph Lennox
by
4.8k points